Topological modulation of metal–thiadiazole dicarboxylate coordination polymers through auxiliary ligand alteration1. Issue 23 (21st June 2015) - Zhao, Zhen-Xin; Li, Yun-Wu; Liu, Sui-Jun; Wang, Li-Fu; Chang, Ze; Xu, Jian; Zhang, Ying-Hui
<x xml:space="preserve">Abstract</x> Five new CoII/ZnII coordination polymers with distinct topological networks have been prepared based on H2tdzdc and different auxiliary ligands. The magnetic properties of the two CoII complexes have been studied in detail.